Therapeutic Effect of Astragali Radix Extract Injection Combined with Bone Marrow Mesenchymal Stem Cells in Bleomycin-Induced Pulmonary Fibrotic Rats. (13th June 2022) - Du, Quanyu; Wu, Xuanyu; An, Liping; Zhou, Rui; Xiao, Xiang; Wu, Cheng; Wang, Fei; Yang, Han
Abstract : Pulmonary fibrosis is a serious disease for which effective drugs are unavailable. Here, we treated rat models of bleomycin (BLM)-induced pulmonary fibrosis with Astragali Radix extract injection (AI) combined with or without bone marrow mesenchymal stem cells (BMSCs). We injected rats intratracheally with BLM and transplanted BMSCs via tail vein injection 15 days later. We also intraperitoneally injected AI daily from days 15 to 28. Changes in lung pathology and function, as well as the levels of matrix metalloproteinases, collagen, C-X-C motif chemokine ligand 12 (CXCL12), and cluster of differentiation 90 (CD90) were assessed. The results revealed that compared with the BLM group, groups treated with ARE and BMSCs (alone or combined) reduced the expression levels of TGF- β 1 and collagens I and III, ameliorated pathological lung fibrotic damage, and improved lung function. The expression levels of MMP-1, MMP-3, and MMP-9 were reduced by either AI or BMSCs alone, whereas those of MMP-3, MMP-9, TIMP-1, CXCL12, and CD90 were elevated by combined AI and BMSCs compared with the BLM group. Overall, these findings demonstrated that AI and BMSCs both can reduce damage caused by PF in rats and that AI altered the expression of chemokines and surface markers in BMSCs.